1997
DOI: 10.1182/blood.v90.4.1649
|View full text |Cite
|
Sign up to set email alerts
|

Metalloproteinases in Multiple Myeloma: Production of Matrix Metalloproteinase-9 (MMP-9), Activation of proMMP-2, and Induction of MMP-1 by Myeloma Cells

Abstract: Multiple myeloma is a very devastating cancer with a high capacity to destroy bone matrix. Matrix metalloproteinases (MMPs) play a critical role in bone remodeling and tumor invasion. In this study, we have investigated the involvement of interstitial collagenase (MMP-1) and gelatinases (MMP-2 and MMP-9) in the biology of multiple myeloma. We show (1) that myeloma cells express MMP-9 and (2) that this expression is not subjected to regulation either by interleukin-6 (IL-6), the major myeloma cell growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(51 citation statements)
references
References 36 publications
5
45
0
1
Order By: Relevance
“…When the MMP‐9 production of this cell line was analyzed, no MMP‐9 activity was observed. This agrees with the data of Barillé et al ,11 who compared the conditioned media of primary myeloma cells (patient SBN‐1) and of the cell line (SBN‐1) established from these myeloma cells. The SBN‐1 cell line, which was immortalized for almost 1 year, had no detectable MMP‐9 activity compared to fresh myeloma cells, which produce a significant amount of MMP‐9.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…When the MMP‐9 production of this cell line was analyzed, no MMP‐9 activity was observed. This agrees with the data of Barillé et al ,11 who compared the conditioned media of primary myeloma cells (patient SBN‐1) and of the cell line (SBN‐1) established from these myeloma cells. The SBN‐1 cell line, which was immortalized for almost 1 year, had no detectable MMP‐9 activity compared to fresh myeloma cells, which produce a significant amount of MMP‐9.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have demonstrated a role of MMPs in cancer. MMP production was demonstrated in MM 11, 14, 28. We used the 5T33MM mouse model to investigate the production of MMP‐9 (gelatinase B) in MM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of studies in haematologic neoplasia concerning MMPs are in vitro studies. In multiple myelomas, increased activity of MMPs can cause the excessive bone marrow resorption and result in spreading the myeloma cells (17–19).…”
Section: Discussionmentioning
confidence: 99%
“…Besides its implication in the inflammatory processes, the relationship between glucocorticoid resistance, HDACs regulation and gene expression modulation can also be of importance for tumor cell progression (23). In multiple myeloma, the MMP-9 plays a critical role in tumor invasion (24)(25)(26). However, the impact of new therapeutics…”
Section: Introductionmentioning
confidence: 99%